Peranan Profetik Leadership Dalam Mengelola Institusi Pendidikan Islam - ANDRE SEPTA (JMPT: Jurnal Manajemen Pendidikan Tihamah, 2023)
In the administration of educational institutions, it is unquestionable that we should emulate the exemplary character of Prophet Muhammad (SAW). The Prophet's effective guidance and leadership serve as a primary source of inspiration that can be implemented in the governance of Islamic educational establishments. This research employs a qualitative descriptive analysis methodology, utilizing a library research approach. The library approach emphasizes the collection of data through the examination of materials such as reference books, journals, and relevant teaching resources. Prophetic leadership entails self-control and genuine influence over others to achieve shared objectives, akin to the actions of the prophets. The existing leadership model in Islamic educational institutions falls short in providing comprehensive solutions, requiring enhancements and refinements. Nevertheless, genuine efforts are underway to instill Indonesian values within prophetic leadership. Overall, adopting prophetic leadership practices serves as a remedy for establishing a robust foundation in educational institution management. This ensures the consistent application of religious teachings and places significant emphasis on character development and the holistic growth of students.